PENGARUH CORPORATE GOVERNANCE, CASH HOLDINGS, TOBIN’S Q, INTENSITAS IKLAN, DAN REGULASI TERHADAP ACQUISITION ABILITY (Studi Empiris pada Perusahaan Non-Keuangan yang Terdaftar di Bursa Efek Indonesia Periode 2016-2019) - Sri Aida Fitriani; Agung Juliarto (Diponegoro Journal of Accounting, 2021)
Today’s market economical business competition pushes companies to obtain acquisition strategy as the best way to keep their existence. Previous studies discussed the motives and impacts of acquisition activities towards bidding firms and targeted firms. Whereas, this study aims to identify and analyze factors effecting firm acquisition ability. The financial factors consist of cash holding, Tobin’s Q, and promotion intensity whilst non-financial factors include corporate governance and regulation. The data is taken from 60 non-financial firms on IDX from 2016-2019 periods by using purposive sampling method and analyzed by using logistic regression. The corporate governance variable is measured by using corporate governance index (CGI score) which is deemed as more comprehensive measure of firm’s governance. The results of this study show that corporate governance and Tobin’s Q significantly affect acquisition ability of firms. However, this study does not find evidence that cash holding, promotion intensity, and regulation variables affect the acquisition ability of a firm. These results prompt managers to consider financial and nonfinancial factors in formulating acquisition strategy.